2019
DOI: 10.1089/ct.2019;31.333-335
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto's Thyroiditis Is a Risk Factor for Thyroid Cancer

Abstract: BackgroundHashimoto's thyroiditis (HT), a common autoimmune disease, is the most frequent cause of hypothyroidism, affecting 2 to 15% of the population (1). Histologically, HT is characterized by diffuse lymphocytic infiltration of the thyroid gland (2). It has been hypothesized that HT, a chronic thyroid inflammatory disease accompanied by positive serum thyroid peroxidase antibody (TPOAb) titers, is associated with an increased risk of thyroid cancer. However, previous studies have not been able to prove thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
(2 reference statements)
0
3
1
Order By: Relevance
“…We speculate whether this autoantibody association might be the cause of this morphological finding, which was not observed in type 3 thyroiditis (with both autoantibodies positive) because Anti-TPO may reduce the expression of Anti-TG in the same gland. In the present study, no patient showed association of HT with malignant neoplasias, even among those with thyroid nodules submitted to FNAB [30,31].…”
Section: Resultscontrasting
confidence: 58%
“…We speculate whether this autoantibody association might be the cause of this morphological finding, which was not observed in type 3 thyroiditis (with both autoantibodies positive) because Anti-TPO may reduce the expression of Anti-TG in the same gland. In the present study, no patient showed association of HT with malignant neoplasias, even among those with thyroid nodules submitted to FNAB [30,31].…”
Section: Resultscontrasting
confidence: 58%
“…PTCs, with associated CLT, show a less extensive disease at diagnosis and improved disease-free survival [82,128], whereas patients with tumor-infiltrating lymphocytes in PTC, without CLT, had a higher disease stage and an elevated incidence of invasion and lymph node metastasis compared to patients without lymphocytes [94]. Different prospective study investigated the association between HT and thyroid malignancy, showing a higher rate of indeterminate cytology and a higher incidence of thyroid cancer in patients with HT [129,130].…”
Section: Chronic Lymphocytic Thyroiditis (Clt) and Tcmentioning
confidence: 99%
“…The stimulated nicotine receptors on immune cells may be involved in the decreased risk of Hashimoto’s thyroiditis ( 23 ). Another tobacco alkaloid, anatabine, also helped to reduce not only the incidence but also the severity of thyroiditis related to thyroglobulin ( 24 ), while a positive relationship between TC and chronic thyroiditis, such as Hashimoto’s thyroiditis, was found in some studies ( 25 , 26 ). However, the relationship between eating habits and TC development stratified by smoking status is still unclear and needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%